Pengaruh Transparansi, Akuntabilitas Dan Konsep Value For Money Terhadap Pengelolaan Keuangan Sektor Publik Pada Badan Pengelolaan Keuangan Dan Aset Daerah (BPKD) Provinsi Papua - Masdianah Masdianah; Klara Wonar; Adolf Z.D Siahay (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2024)
This research aims to determine the influence of transparency, accountability and the concept of value for money on public sector financial management at BPKAD Papua Province. This type of research is associative. The sample in this study was 50 state civil servants in the secretariat sector, budget sector, district/city financial development sector, regional treasury and cash sector, regional asset management sector and accounting sector. The data sources used in this research are primary data and secondary data. Data collection techniques using questionnaire data. The data analysis techniques used in this research consist of descriptive statistical tests, validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis tests, t-tests, f-tests, and coefficient of determination tests using applications. IBM SPSS version 23. The research results show that the variables of transparency, accountability and the concept of value for money have a positive and significant effect on public sector financial management at BPKAD Papua Province.